The Very Noisy Night - Hendry, Diana, 1941-; Chapman, Jane, 1970- (Wilton, CT : Tiger Tales, 2020)
Disturbed by the many peculiar sounds he hears while trying to get to sleep, Little Mouse repeatedly asks to get into bed with Big Mouse.
"Originally published in Great Britain 1999 by Little Tiger Press Ltd."--Page facing title page.
On board pages with padded cover.
Keywords: Board books; Sound -- Fiction; Bedtime -- Fiction; Night -- Fiction; Mice -- Fiction; Board books; Fear -- Fiction; Picture books